Eat well to the best performance: calorie intake and eating behavior among athlete: a review - Wati, Isti Dwi Puspita; Kusnanik, Nining Widyah; Wahjuni, Endang Sri; Samodra, Yohanes Touvan Juni; Gandasari, Maharani Fatima; Sofyan, Davi (Intelektual Pustaka Media Utama, 2024)
Good performance can be produced from a structured, systematic, and continuous training pattern. However, a lack of calorie intake during exercise will worsen the athlete's performance. Adequate and appropriate calorie intake can help athletes perform well. Eating habits will greatly affect the availability of calories in athletes. This literature review aims to describe the effects of caloric intake and eating habits of athletes from various literature. Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) is the approach employed. The database is taken from Scopus, Science Direct, Web of Science (WOS), and Pubmed. 16 articles were analyzed through purpose, topic suitability, sample, research protocol, results, and discussion. The results of this literature review explain that athletes tend to experience less calorie intake caused by poor eating habits. Low knowledge of nutrition makes athletes practice wrong eating/dieting arrangements by relying on supplement intake to improve performance.